Investigating public sector client performance in South African construction procurement - Saad, Mohammed Mustapha (My University, 2017)
This study proceeds from the premise that the dissatisfaction of the clients with the outcomes of the construction projects stems from their objectives not being met by the industry. The study aimed at investigating public sector clients’ performance in the South African construction procurement with a view to establishing how their efficiency and effectiveness could be improved during procurement processes. The specific research objectives are to: identify the key performance indicators (KPIs) for public sector clients in their procurement process; assess and analyse the weaknesses and strengths associated with public sector clients’ performance in the construction procurement process; develop a methodical approach to the measurement of public sector clients’ performance in their procurement processes; and recommend implementable approaches to improving client performance in the public sector procurement process. A qualitative and quantitative mixed method research design was adopted in carrying out the study. This involved the use of interviews and structured questionnaire survey. Data were collected from National and Provincial Departments of Public Works as public sector client representatives in South Africa. Based on the analysis of the organogram, a total of six functional units involved in the procurement process were identified and targeted for the purpose of data collection. The purposive sampling technique was adopted for the study. These are Heads of Departments, Deputy Directors General responsible for construction projects, Chief financial officers, Heads of supply chain management, Heads of human resources management, and senior project managers. Information collected included issues leading to uncovering of public sector key performance indicators (KPIs) and strengths and weaknesses associated with public sector clients’ performance. Data collected were analysed using content analysis to determine the themes and constructs leading to the identification of public key performance indicators. Further analysis was carried out using mean ranking analysis of factors associated with the strengths and weaknesses associated with public sector clients’ performance. The results of the research show project delivery process as good, not excellent; no detailed template for clarifying project briefs; legislative and administrative procedures lead to time and cost overruns; lack of adequate capabilities within in-house trained professionals and technical expertise to supervise all projects, insufficient in-house professionals to be represented on each project site; lack of mechanism to monitor in-house professionals’ participation on project sites; low participation of end users’ agents due to high incapacitation of User Department organisation; DPW are highly incapacitated because of lack of standard documentations; lack of professional training and short courses to enhance the skills and expertise of technical professionals. Other results show that delayed/late payment to contractors and end user agents due to cash flow challenges; weak or neglect of project monitoring and supervision; disputes between project managers and consultants as a result of quality of work done by contractors; bureaucratic bottlenecks and long decision making processes; design changes and variation due to contingent events, unforeseen circumstances due to weather, earthworks, disasters, changes in User Department briefs and challenges due to administration and political issues. The findings could also be drawn from challenges in descending order of importance from the human resources management units, the financial management units, the supply chain management units, project management units, decision making processes, planning units, design, briefing, documentation and policy issues. The study concluded that 137 public sector key performance indicators are identifiable for assessing public sector client performance in South African procurement. It also concluded that out of several challenges, the human resources, financial management, supply chain management, and project management challenges are the most severe challenges that beset the National and Provincial Department of Public Works, while the documentation and policy issues are less severe. Implementable recommendations were made to specific user departments. The human resources management units in the South African National and Provincial Departments of Public Works should adopt the recommendation suggested in this study to improve the effectiveness and efficiency of professionals during their project delivery process.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Building to the Faculty of Engineering and Built Environment, University of the Witwatersrand , Johannesburg, 2017
Keywords: Contractors--South Africa; Construction industry--South Africa; Project management--South Africa